Exploring the Attendance and Potential Benefits of Reducing Sitting Time for Residents in a Canadian Long-Term Care Setting: A Pilot Study. (December 2020) - Lee, Amanda; Sénéchal, Martin; Read, Emily; Bouchard, Danielle R.
Background: This study aimed to assess the attendance to a novel intervention aiming to reduce sitting time in a long-term care facility and exploring the potential functional benefits.Methods: The intervention consisted of research staff visiting a resident to promote standing for 10-minute sessions, three times per day (morning, afternoon and evening), 4 days per week (Monday-Wednesday-Friday and Sunday) over 10 weeks. The main outcome was attendance. Functional outcomes included walking speed, power, and strength.Results: A total of 28 participants agree to participate and 24 completed the trial. The average attendance averaged four sessions per week and averaged 45 minutes of standing weekly out of 120 minutes offered. Attendance was highest during the morning session ( p  = .02) and weekdays ( p  < .01). There was a significant improvement in the 30-second chair stand test ( p  < .05).Conclusion: Although well accepted, the attendance was low. Based on the information gathered suggestions can be made to improve the intervention, attendance, and potential benefits of such intervention.